2013
DOI: 10.1101/gr.152140.112
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of regulatory activity across diverse human cell types predict tissue identity, transcription factor binding, and long-range interactions

Abstract: Regulatory elements recruit transcription factors that modulate gene expression distinctly across cell types, but the relationships among these remains elusive. To address this, we analyzed matched DNase-seq and gene expression data for 112 human samples representing 72 cell types. We first defined more than 1800 clusters of DNase I hypersensitive sites (DHSs) with similar tissue specificity of DNase-seq signal patterns. We then used these to uncover distinct associations between DHSs and promoters, CpG island… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
226
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(236 citation statements)
references
References 64 publications
10
226
0
Order By: Relevance
“…Our analysis therefore shows that Xa-specific methylation is associated with loss of active histone marks in males at genomic regions that have previously been implicated in sex-specific roles in X inactivation. 34 Therefore, we provide preliminary evidence for a role of DNA methylation on the active X in maintaining sex-specific accessiblechromatin patterns. However, this appears limited to only a few specific loci, and is not a widespread phenomenon.…”
Section: Xa-specific Methylation Is Associated With Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis therefore shows that Xa-specific methylation is associated with loss of active histone marks in males at genomic regions that have previously been implicated in sex-specific roles in X inactivation. 34 Therefore, we provide preliminary evidence for a role of DNA methylation on the active X in maintaining sex-specific accessiblechromatin patterns. However, this appears limited to only a few specific loci, and is not a widespread phenomenon.…”
Section: Xa-specific Methylation Is Associated With Genesmentioning
confidence: 99%
“…Remarkably, LOC286467 was previously identified as the only locus besides XIST with sex-specific RNA polymerase 2 binding, 33 and along with XIST, LOC550643 was the only locus with sex-specific DNAse I hypersensitivity patterns. 34 Unfortunately, the Infinium HM450 array did not cover the gene body of LOC550643, which showed H3K4me3 enrichment in females from the BLUEPRINT data. Our analysis therefore shows that Xa-specific methylation is associated with loss of active histone marks in males at genomic regions that have previously been implicated in sex-specific roles in X inactivation.…”
Section: Xa-specific Methylation Is Associated With Genesmentioning
confidence: 99%
“…This situation is the rule rather than the exception, 18 because SNPs are usually stronlgy correlated to dozens of nearby SNPs, up to distances of 100 19 kbp. This non-random correlation between nearby SNPs is referred to as linkage disequilibrium 20 (LD) and occurs due to the common descent of humankind from a relatively small ancestral 21 population.…”
mentioning
confidence: 99%
“…To test the ability for using genome-wide functional genomics tracks to 262 help distinguish causal from merely correlated SNPs, we used DNase-seq data to measure DNA 263 accessibility, published by the ENCODE project [10]. We normalized the DNase-seq data for 264 112 human samples, as described previously by Sheffield et al [19].…”
mentioning
confidence: 99%
“…2,23,24 Based on this latter function and on the identification of conserved CTCF binding events across various cell-types and tissues, [25][26][27] this TF was proposed to fulfil a general chromatin organization role. 28 At the same time, specific roles for CTCF in neuronal and haematopoietic cell differentiation had been defined. 29 In this context, detailed analyses of CTCF cistromic studies revealed the existence of cell type-specific chromatin binding sites.…”
mentioning
confidence: 99%